Diabetes and obesity burden and improvements in cardiometabolic parameters in patients with psoriasis or psoriatic arthritis receiving apremilast in a real-world settingCapsule Summary - Cristi Cavanaugh, MHS; Kate Orroth, PhD, MPH; Xi Qian, PhD; Pam Kumparatana, MSW, MPH; Yuri Klyachkin, PhD; Stephen Colgan, PhD; Myriam Cordey, PhD, MPH (Elsevier, 2024)
Introduction: Patients with psoriasis and psoriatic arthritis have a higher prevalence of cardiometabolic comorbidities compared to the general population. Clinical data suggest apremilast may reduce weight and glycated hemoglobin (HbA1c). Objective: To describe changes in cardiometabolic parameters among patients with psoriasis and psoriatic arthritis newly treated with apremilast by prediabetes/diabetes or obesity status. Methods: This was a retrospective cohort study of electronic medical records from patients with psoriasis and/or psoriatic arthritis in the OM1 Real-World Data Cloud who newly initiated apremilast. Changes from baseline in body mass index, weight, HbA1c, and lipids were evaluated at 6 and 12 months using a multivariable linear regression model stratified by prediabetes/diabetes or obesity status. Results: Of 8487 patients initiating apremilast, 24% had diabetes. Of 8250 patients with body mass index available, 27% were obese and 34% were severely obese. Patients experienced decreases in body mass index and weight at 6 and 12 months regardless of diabetes or obesity status, with the greatest reductions seen in those with diabetes and obesity. Reductions in HbA1c at 6 months were seen in patients without diabetes and patients with severe obesity. Conclusions: Treatment with apremilast may provide the greatest cardiometabolic benefit to those with the greatest burden of cardiometabolic disease.